A sensitive cut: the passage between centuries I BC and II AD in Historiography - Degan, Alex (Romanitas - Revista de Estudos Grecolatinos, 2015)
This article problematizes the proposals for periodization of the history of Judaism (1st century BC and 2nd century AD), observing historiographical debates from the 19th to the 21st.
Keywords: History; Historiography; Judaism; Periodization